Uncovering Customer Value in the Cardiac Rhythm Management Industry in Malaysia - Lee, Augustin Kuan Lock (2013)
In the Cardiac Rhythm Management (CRM) industry in Malaysia, customer value is derived from multiple touch points between the electrophysiologist (EP) and the industry employed allied professional (IEAP). Due to the hybrid nature of the product service elements of this business-to-business (B2B) interaction, according to industry assumptions, value to the customer is created along several dimensions such as product quality, service support and price. Customer value has been linked to customer satisfaction and competitive advantage and deserves important management consideration (Saeed 2005, Woodhall 2003, Woodruff 1997). Therefore, this paper aims to uncover what constitutes customer value in this industry and which of these factors is more important than others. Ulaga and Eggert 2006 customer value relationship framework with its constructs such as product quality, delivery performance, service support, personal interaction, supplier know how, relationship value and direct cost / price, was the dominant model for this paper. Other pertinent value constructs for this research such as social benefits, confidence benefits and switching cost were also included. The survey questionnaire was emailed to all cardiologists who offered CRM services to their patients and response rate was 54%. Product quality, direct cost / price and service support were identified as the most value creating dimensions of this relationship while social benefits and switching cost were ranked at the bottom. The implication of these results is industry players should continue to allocate resources in these value creation dimensions in order to differentiate itself to attain key supplier status.